Notes on eggs, larvae and juveniles of fishes from Indian waters III. Katsuwonus pelamis (Linnaeus) and IV. Neothunnus macropterus (Temminck and Schlegel) - Jones, S (Indian Journal of Fisheries, 2016)
In this article, larval stages of the oceanic skip-jack, Katsuwonus pelamis (Linnaeus) collected from the Laccadive Sea during the cruises on board the Research Vessel Kalava are described. Though the adults of this species are caught only rarely from the coastal waters of the mainland of India, it is found in appreciable numbers around the islands of the Laccadive Archipelago and forms a very important fishery in the Southern Island of Minicoy (Jones and Kumaran, 1959).